Learning Media: PowerPoint vs Prezi - Ummul Hasanah; Suhardiman (IJER (Indonesian Journal of Educational Research), 2022)
The research purpose was to determine the difference of biology learning outcome by implementation of PowerPoint media and Prezi media on students of class X of MAN 2 Model Makassar. The research is quasy experimental research and it used intac group comparison design. The measurement of learning outcome was done by giving valuating test (posttest) in ecosystem matter. Collected data was analyzed using descriptive statistical and inferential statistical analysis. The result of statistic descriptive showed that the average of biology learning outcome of the comparison class was 78.44 and the compared class was 73.05. Analysis of data using a test value t p (Sig. 2-tailed) 0.036 < 0.05 so H0 rejected and H1 accepted. From the research results can be concluded that there are differences in biology learning outcomes by implementation of PowerPoint media and Prezi media on students of class X of MAN 2 Model Makassar.